Analysis of Pre-Service Science Teachers’ Technological Pedagogical Content Knowledge (TPACK) Ability in Online Learning - Arif Widiyatmoko; Dyah Rini Indriyanti; Kao Sovansophal; Melissa Salma Darmawan; Tiara Dwi Wulandari (Journal of Innovation in Educational and Cultural Research, 2025)
The development of Information, Communication, and Technology (ICT) impacts Education 5.0 to improve the quality and equity of education services in Indonesia, especially in science learning. This study aims to analyze the ability of pre-service science teachers to use TPACK (Technology Pedagogical Content Knowledge) in online learning. The survey research method is used to get information about TPACK pre-service science teachers' ability to carry out online learning. The sample consisted of 132 pre-service science teachers from education Universities in Indonesia. The research instrument consisted of 42-item questionnaires that assessed TPACK components in online learning. The results showed that the percentage of pre-service science teachers' average score on TPACK ability is 79.87%. The percentage of average scores for each component TPACK is 78.68% for Pedagogical Knowledge (PK), 79.54% for Content Knowledge (CK), 80.73% for Technological Knowledge (TK), 78.94 for Pedagogical Content Knowledge (PCK), 81.73% for Technology Pedagogical Knowledge (TPK), 80.98% for Technology Content Knowledge (TCK), and 78.64% for TPACK. The highest average scores on TPACK are TPK, TCK, and TK. It is concluded that pre-service science teachers' TPACK skills in online learning related to the use of technology are superior to content knowledge and pedagogy.